BURNOUT AND STRESS AMONG HEALTHCARE PROFESSIONALS. A SCIENTIFIC REVIEW. - Ahmed Hasan Mohamed Alomri, Wail Abdullah Salem Alsubhi, Basmah Mohammed Hasan Aljehani, Maryam Mohammad Hassan Rajeh, Ghadah Hamed Mutlaq Alrefai, Yahia Saleem Alamri,; Hamad Waslallah Wasel Almaramhi, Khaled Tariq Abdullah Al-Ghamdi, Amal Hassan Alharbi, Naif Ahmed Alharbi, Abdulkarim Qasim Khaishan Alshaikh, Mohammed Hamoud Saleh Almaymoni, Khadijah Saleem Alrowaili (Chelonian Research Foundation, 2022)
Stress is an intrinsic occurrence that is unavoidable, especially in a professional setting, and it negatively impacts the quality of one's existence. The disorder in question has a global impact, particularly among health professionals, and is caused by a multitude of factors.The aim of this review article are to study stress and burnout among health professionals in order to clarify the definition, identify possible causes and related factors, and identify coping strategies.This review article was performed through databases such as PubMed,Scopus and Web of Science.Stress affects individuals of any age and professional area. When it is caused by work complications, it is called occupational stress. This phenomenon results from the action of an agent stressor that can be physical, social, or even psychological. Another phenomenon is burnout syndrome, which is characterized by emotional exhaustion, a lack of professional accomplishment, and depersonalization. To mitigate the effects of stress, there are specific mechanisms of coping.Stress and burnout are quite prevalent phenomena among health professionals. As these professionals have a fundamental role in patient care, it is extremely important that they feel well physically and psychologically to fulfill their functions as caregivers. In this way, it becomes important to act in the relationship between the individual and the problem, improving the skills of encouraging and using his social and personal resources to obtain control over the circumstances that induce stress. Keywords: burnout syndrome; coping; health professionals; occupational stress; stress